Oilseed meals into foods: an approach for the valorization of oilseed by-products - Nevara, Gita Addelia; Ibrahim, Shafa’atu Giwa; Syed Muhammad, Sharifah Kharidah; Zawawi, Norhasnida; Mustapha, Nor Afizah; Karim, Roselina (Taylor Francis Group, 2022)
The excellent health benefits of oil extracted from seeds have increased its application in foods, pharmaceutical and cosmetic industries. This trend leads to a growing research area on their by-products, oilseed meals, to minimize environmental and economic issues. Examples of these by-products are soybean, peanut, kenaf seed, hemp, sesame, and chia seed meals. It is well known that soybean meals have wide applications in food and non-food industries, while other seed meals are not well established. Most oilseed meals are rich in health beneficial compounds and are potential sources of plant protein, dietary fiber, and antioxidants. Many studies have reported on the valorization of these by-products into value-added food products such as bakery and meat products to increase their nutritional and functional properties. These efforts contribute to the sustainability, development of novel functional food and support the zero-waste concept for the environment. This review aims to provide information on the composition of selected oilseed meals from soybean, peanut, hemp, kenaf, sesame and chia seeds, their potential applications in the bakery, meat, beverage, pasta, and other food products, and to highlight the issues and challenges associated with the utilization of oilseed meals into various food products.